Functionalized SBA-15 and its catalytic applications in selective organic transformations - Srinivas, Darbha; Saikia, Lakshi (Catalysis Surveys from Asia, 2008)
Ordered, mesoporous SBA-15 functionalized with organic and inorganic moieties exhibits efficient catalytic activity in a variety of organic transformations. In this account, reviewing our own work, three-sets of surface-modified SBA-15 materials have been investigated. The first-set of materials consists of SBA-15 modified with organo-acidic (propyl thiol and propyl sulfonic acid) and basic (propyl amine and propyl adenine) moieties. The second-set of materials was prepared by grafting Mn complexes to the organo-functionalized SBA-15. The third-set composes of nanocrystalline metal oxides supported on SBA-15. All these catalysts have been characterized by structural and spectroscopic techniques. Catalytic activities of the first-set of solid materials have been investigated in acid/base-catalyzed reactions viz., ring-opening of epoxides with amines (producing beta-amino alcohols), esterification, three-component-Mannich reactions and cycloaddition of CO(2) to epoxides. The Mn complexes grafted on organofunctionalized SBA-15 are efficient catalysts for the chemo-, regio- and stereoselective aerial oxidation of monoterpenes at ambient conditions. TiO(x), VO(x), MoO(x) and WO(x) supported on SBA-15 catalyzed biomimetic oxyhalogenation of aromatic compounds. In all these reactions, the functionalized SBA-15 showed high selectivity.
Keywords: grafted Mn-Salen complexes; Ordered mesoporous silica; organofunctionalized SBA-15; oxidation catalysts; Oxyhalogenation of aromatics

Regiospecific oxyhalogenation of aromatics over SBA-15-supported nanoparticle group IV-VI metal oxides - Saikia, Lakshi; Rajesh, M.; Srinivas, Darbha; Ratnasamy, P. (Catalysis Letters, 2010)
TiO(x), VO(x), MoO(x) and WO(x) supported on SBA-15 exhibit efficient catalytic activity for oxyhalogenation of aromatics with the H(2)O(2)-halide ion system. Unlike the hitherto known solid catalysts, these reusable catalysts yield the para-halogenated product with 100% selectivity at 298 K and moderate acidic pH (3-5). The catalytic activity was enhanced by five orders of magnitude when supported on SBA-15.
Keywords: Haloperoxidase activity; Ordered mesoporous silica; Oxyhalogenation of aromatics; SBA-15; Supported metal oxides

Efficient olefin epoxidation with high turnover rates over ordered mesoporous silica nanoparticles with uniform manganese sites - Negi, Sanjay Singh; Khatri, Prateek; Singh, Anand Pal (Microporous and Mesoporous Materials, 2023)
Olefin epoxidation has been studied over a series of mesoporous manganese silicate nanoparticles and tBuOOH. Partial substitution of Si by Mn in silica framework leads to highly dispersed, distorted Mn(III) sites, confirmed by various physicochemical analyses. High conversion and stable styrene oxide, stilbene oxide and epoxy cyclohexane yield have been achieved with MS75 with 1:1.5 ratio of olefin: oxidant. However, at faster reaction rates lower styrene oxide yield is observed at lower Mn-containing catalyst (MS100). High TON, TOF over manganese sites shows accessible monomeric Mn sites. Attributed to high reactant density at redox-active Mn silicate sites due to facile diffusion across shallow pore depth channels of nanoparticulate om-MSx and surface hydrophobic characteristics. The catalysts were found to be stable under recycling and filtration experiments. The excellent stability against leaching of active manganese species indicates stable sites and good textural properties in om-MSx, essential for extended activity.
Keywords: epoxidation; Manganese silicates; Mesoporous silica nanoparticles; Ordered mesoporous silica; pH adjustment